Birds of a Feather: Alexander McQueen’s Victorian Bestiary - Ariane Fennetaux (Cahiers Victoriens et Edouardiens)
With fur, feathers, corals, antlers or butterflies a constant feature of his creations, Alexander McQueen created designs that gave the animal world pride of place whilst his fashion and the imagery of his catwalk presentations were deeply influenced by Victorian sartorial and visual culture. In this essay the Victorian inspiration of his retro-futuristic designs will be studied to illustrate the uncanny persistence of some of the animalistic fantasies of the Victorian era into the contemporary world. McQueen not only played with Victorian sartorial and animal references but also mixed and matched humans, animals and indeed machines and cross-fertilized them into single creatures thus borrowing from the Victorians not only their bestiaries but also, Frankenstein-like, sewed together parts of different animals to create monstrous hybrids, indeed discomforting animals.